1992
DOI: 10.1148/radiology.185.1.1523339
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of spot compression-magnification and tangential views in mammographic evaluation of palpable breast masses.

Abstract: To define the role of special mammographic views in evaluating palpable breast masses, 70 consecutive women with palpable breast masses underwent standard two-view examination of each breast and spot compression-magnification and tangential view examination of the palpable mass. Thirty palpable masses were found in 30 patients (43%). Standard views depicted 26 masses (87%). Tangential views also depicted 26 masses. Some of the masses seen on tangential views were not seen on standard views and vice versa. Spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, zooming display in soft-copy reading may not attenuate the role of magnification mammography in other clinical situations, including the evaluation of mammographic abnormalities, such as asymmetry and distortion, and evaluation of the lesion once again under different positions [13,14]. Magnification mammography would still be useful for the characterisation of asymmetry or distortion using a spot-compression paddle and for the confirmation of layering calcification in cases of ''milk of calcium'' using a true lateral view.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, zooming display in soft-copy reading may not attenuate the role of magnification mammography in other clinical situations, including the evaluation of mammographic abnormalities, such as asymmetry and distortion, and evaluation of the lesion once again under different positions [13,14]. Magnification mammography would still be useful for the characterisation of asymmetry or distortion using a spot-compression paddle and for the confirmation of layering calcification in cases of ''milk of calcium'' using a true lateral view.…”
Section: Discussionmentioning
confidence: 99%
“…DBT in standard views and CSC are both clinically available for patients who have ambiguous findings on FFDM, such as vague masses, architectural distortions, and asymmetries 11 14 . DBT in standard views not only shows more detailed structures of lesions but also helps to localize one-view findings.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1968, spot compression has been reported to aid FFDM in evaluating abnormalities or distinguishing real lesions from fake ones created by superimposed breast tissue 12 14 . It was a common method for further evaluation of suspicious lesions on FFDM.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Faulk and Sickles found, in a study of the efficacy of spot compression-magnification and tangential views in the mammographic evaluation of palpable breast masses, that spot compression-magnification views depicted 97% of the masses; whereas, standard views depicted 87%. 7 Tangential views also depicted 87% of the masses with some of the masses that were detected in tangential views not being detected in the standard views and vice versa. In addition, they found that use of special views enabled radiologists to correctly predict benign or malignant status in 77% of cases as compared with correct prediction in 69% of cases with only standard views.…”
Section: Introductionmentioning
confidence: 99%